Does Financial Structure Matter in Determining the Effectiveness of Monetary Policy? A Comparison Between Civil-Law and Common-Law Countries - Zukarnain Zakaria (Asian Academy of Management Journal of Accounting and Finance, 2008)
This paper compares the effectiveness of monetary policy between civil-law and common-law countries by using the impulse response of monetary policy on the level of investment and consumption. This comparison is made to determine whether countries of common-law origin are less sensitive to monetary policy actions compared with civil-law countries. Theoretically, we expected monetary policy is to be more effective in civil-law countries, in which financial structures are generally more bank-based as compared to common-law countries, in which financial structures are more market-based. The impulse response functions were generated through the estimation of first-differences VAR. The findings show that the impact of monetary policy on investment and consumption is relatively stronger, responds more quickly and is long lasting in civil-law countries compared with common-law countries.